2005
DOI: 10.1007/s10493-005-1271-1
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Dermacentor silvarum (Acari: Ixodidae) under laboratory conditions

Abstract: The minimum life cycle of Dermacentor silvarum Olenev had a mean duration of 87.5 days (range 74-102 days) under laboratory conditions [(27 +/- 1 degrees C), 70% RH, 6 L: 18 D]. The mean time in (days) for the different stages of its cycle was as follows: incubation period of eggs was 15.3 days; prefeeding, feeding and premoulting periods of larvae and nymphs averaged 5.5, 4.0 and 7.3 days, and 5.2, 5.0 and 14.6 days, respectively; prefeeding, feeding, preoviposition and oviposition periods of female adults la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 11 publications
1
44
1
Order By: Relevance
“…microplus, found high correlations between tick weight and the number of eggs laid and eggs hatched. Other authors have found similar relationships in other species of ticks (DRUMMOND; WHETSTONE, 1970WHETSTONE, , 1975DRUMMOND et al, 1971;WANCHINGA;BARKER, 1986;KOCH, 1982;LIU et al, 2005). The results of this study agree with these previous reports in the literature.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…microplus, found high correlations between tick weight and the number of eggs laid and eggs hatched. Other authors have found similar relationships in other species of ticks (DRUMMOND; WHETSTONE, 1970WHETSTONE, , 1975DRUMMOND et al, 1971;WANCHINGA;BARKER, 1986;KOCH, 1982;LIU et al, 2005). The results of this study agree with these previous reports in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested by Passos dos Santos and Furlong (2002) that heavier females produce more eggs and thus have a higher REI. The REI and RAI observed in this study were higher than those reported by other authors (BORGES et al, 2001;CHILTON, 1992;LIU et al, 2005). The quadratic and linear trend observed in this study should be considered normal due to existent variations in female weight increase and the decrease of their capacity to lay eggs.…”
Section: Discussioncontrasting
confidence: 56%
“…Colonies of these ticks were reared on rabbits as described by Liu et al (2005) and maintained in our laboratory. Rabbits were maintained in a room with 50% relative humidity (RH) at 25-27°C and exposed to daylight.…”
Section: Collection and Rearing Of Ticksmentioning
confidence: 99%
“…Several collected ticks were stored under Ϫ80°C conditions. Others were reared on rabbits as described by Liu et al (20). Before DNA extraction, all tick samples were sterilized as described by Clay et al (21) and dissected tissue samples were washed three times in sterile phosphate-buffered saline (PBS) (137 mM NaCl, 2.7 mM KCl, 4.3 mM Na 2 HPO 4 ·7H 2 O, 1.4 mM KH 2 PO 4 , pH 7.4).…”
mentioning
confidence: 99%